The regulation and potential role of interleukin-32 in tuberculous pleural effusion - Wang, Xuan; Yang, Chengqing; Quan, Chao; Li, Jun; Hu, Yan; Liu, Peng; Guan, Lulu; Li, Li (Frontiers in Immunology, 2024)
The possible protective effect of IL-32 in Mycobacterium tuberculosis (Mtb) infection has been indicated. However, few studies have been focused on IL-32 in tuberculosis patients, additionally, the regulation of IL-32 production has rarely been reported. In the present study, the production, regulation and the role of IL-32 in tuberculous pleurisy (TBP) was investigated. We found that the content of IL-32 in tuberculous pleural effusion (TPE) was higher than the level in the malignant pleural effusion and transudative pleural effusion. The level of IL-32 mRNA in pleural fluid mononuclear cells (PFMCs) was higher than those in peripheral blood mononuclear cells (PBMCs) of patients with TBP, and this difference was mainly reflected in the splice variants of IL-32α, IL-32β, and IL-32γ. Compared with the PBMCs, PFMCs featured higher IL-32β/IL-32γ and IL-32α/IL-32γ ratios. In addition, LPS, BCG, and H37Ra stimulation could induce IL-32 production in the PFMCs. IL-32 production was positively correlated with the TNF-α, IFN-γ, and IL-1Ra levels in TPE. Whereas IFN-γ, but not TNF-α or IL-1Ra, could induce the production of IL-32 in PFMCs.Furthermore, IL-32γ could induce the TNF-α production in PFMCs. Monocytes and macrophages were the main sources of IL-32 in PFMCs. Nevertheless, direct cell-cell contact between lymphocytes and monocytes/macrophages played important role in enhancing IL-32 production by monocytes/macrophages cell. Finally, compared with the non-tuberculous pleural effusion, the purified CD4 + and CD8 + T cells in TPE expressed higher levels of intracellular IL-32. Our results suggested that, as a potential biomarker, IL-32 might play essential role in the protection against the Mtb infection in patients with TBP. However, further studies need to be carried out to clarify the functions and mechanisms of the IFN-γ/IL-32/TNF-α axis in patients with TBP.